2005
DOI: 10.1152/ajpheart.00207.2004
|View full text |Cite
|
Sign up to set email alerts
|

Remote preconditioning reduces ischemic injury in the explanted heart by a KATP channel-dependent mechanism

Abstract: Local and remote ischemic preconditioning (IPC) reduce ischemia-reperfusion (I/R) injury and preserve cardiac function. In this study, we tested the hypothesis that remote preconditioning is memorized by the explanted heart and yields protection from subsequent I/R injury and that the underlying mechanism involves sarcolemmal and mitochondrial ATP-sensitive K ϩ (KATP) channels. Male Wistar rats (300 -350 g) were randomized to a control (n ϭ 10), a remote IPC (n ϭ 10), and a local IPC group (n ϭ 10). Remote IPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 21 publications
2
69
0
9
Order By: Relevance
“…On a cellular basis, RIPC seems to use similar mechanisms to exert protection to the target organs that have already been described for local preconditioning (41)(42)(43). For the heart, Hausenloy and Yellon (25,29,44) postulated that ischemic preconditioning leads to activation of prosurvival Akt and p42/44 pathways, which result in antiapoptotic effects and protect the organ against I/R injury.…”
Section: Effects Of Mmp-2 and Mmp-9 On Hypoxia-induced Intracellular mentioning
confidence: 86%
“…On a cellular basis, RIPC seems to use similar mechanisms to exert protection to the target organs that have already been described for local preconditioning (41)(42)(43). For the heart, Hausenloy and Yellon (25,29,44) postulated that ischemic preconditioning leads to activation of prosurvival Akt and p42/44 pathways, which result in antiapoptotic effects and protect the organ against I/R injury.…”
Section: Effects Of Mmp-2 and Mmp-9 On Hypoxia-induced Intracellular mentioning
confidence: 86%
“…A bolus of 1,000 IU/kg heparin (Leo Pharma, Copenhagen, Denmark) was given through the femoral vein. The heart was cannulated in situ, mounted in a Langendorff apparatus and perfused retrogradely with KrebsHenseleit solution at a pressure of 80 mmHg as previously described [16,17]. All hearts were subjected to 40 min preischaemic stabilisation.…”
Section: Isolated Heart Preparationmentioning
confidence: 99%
“…Remote limb preconditioning of a pig that had received a donor heart was able to reduce myocardial infarct size in the denervated donor heart, providing strong evidence that a humoral mediator was responsible for RIPC protection, although an afferent sensory nerve pathway from the limb cannot be excluded [168]. A similar type of study was conducted by Kristiansen and colleagues [169] who demonstrated that hearts excised from a rat that had been remote limb preconditioned experienced a smaller infarct size, when subjected to IRI. Other studies have investigated whether endogenous substances such as adenosine [170], bradykinin [171], opioids [172], CGRP [173], and endocannabinoids [174], are released from the remote organ during the preconditioning ischemia and are carried to the heart in the blood stream where they then activate intracellular pathways of cardioprotection.…”
Section: Evidence For a Potential Humoral Factor In Ricmentioning
confidence: 80%
“…Clearly, further work needs to be undertaken to examine the role cardiac nerves contribute to delayed IPC. In this respect, hearts excised from remote limb preconditioned rats generated smaller infarcts on the Langendorff-apparatus [169], suggesting that cardiac innervation at the time of infarction may not be necessary for cardioprotection, presumably because the heart was already in a preconditioned state.…”
Section: Neural Pathways In Cardioprotectionmentioning
confidence: 99%